The Legal Aspect of Dual Citizenship Enactment in Indonesia: Demand of the Diaspora - Tri Taruna F; Putu Arya Wibisana (Journal La Sociale, 2020)
The demand of the Diaspora for the enactment of dual citizenship has not been fulfilled by the Indonesian Government since the state still subscribes to the principle of “one person one citizenship.”This single citizenship principle has been adhered to since the independence of Indonesia, stemming from the 1945 Constitution as the highest state law, Law no. 3 of 1946 on Citizens and Residents of the State, Law no. 62 of 1958 on the Citizenship of the Republic of Indonesia, up until the Law no. 12 of 2006 as the current Citizenship Law of the Republic of Indonesia, which is currently applicable. In the present, the Government has issued a policy alternative in the form of Indonesian Overseas Card to ensure the civil rights of citizens and foreigners of Indonesian national descent who reside overseas so that they can enjoy facilities in Indonesia. This policy is also intended to revise the validity period for Visit Visa to be applicable for several visits and the period of residence permit, specifically for foreigners who are former citizens of Indonesia and their families, as a means of accommodating the diaspora’s demands. With the issuance of the policy, there is a recognition towards the existence of the Indonesian diaspora overseas as one of the non-state actors for international relations and as agents of change for their homeland.